Filipino building beliefs and how they influenced architecture - Alarcon, Norma I. (2004)
Filipinos are a deeply religious people. Many past events of historical interest attest to the significant role of religion in their everyday life. Early Filipinos were animists who believed in the existence of a supreme being whom the Tagalogs referred to as Bathala. The Ilocanos call him Kabunyan and he is called Laon or Aba by the Bisayas. This animism was further strengthened by the early migrants from Island Southeast Asia who were themselves animists. Like them, our ancestors worshipped the sun (the source of life and energy), the birds, the trees, the mountains and the hills, and the rivers, brooks, and lakes. The early religious worship included the veneration of the spirits and the ancestors. The early Filipinos believed in the cult of the dead and, in addition, the cult of the spirits. They also believed in the offering of sacrifices to appease their gods. In the absence of temples, sacrifices and the accompanying rituals took place in their own homes, at sea or the rivers. or sometimes in the mountains and open fields. Our forefathers believed in the underworld where creatures that can cause unexplainable misery lived. However, there were also powerful talisman or agimat that were used against these creatures. Moreover, Filipinos had beliefs that normally guided their way of life. With these beliefs, they devised means to counteract the consequences and effects that might befall them in some extreme cases. These beliefs persisted even with the introduction of Christianity, which was coupled with new expressions and things associated with the new faith. Folk Christianity was born out of the weaving of Christianity and traditional folk beliefs. In the mid-1980s, the Chinese feng shui (literally wind and water) found its way in the country, particularly in building construction. Today, the consideration of traditional building beliefs that often preceded a construction seemed to have been lost and forgotten. This paper would like to recollect on these various superstitious beliefs and how they influenced house architecture before the feng shui era. These will include the site selection procedure, the months, days and seasons for building a house, the rituals before starting construction, and the beliefs and their attendant consequences of good health and family life, as well as protection from evil spirits.